Determinants of youth’s political knowledge among students in UiTM Campus Samarahan 2 / Mohammad Haikal Mohammad Ali - Mohammad Ali, Mohammad Haikal (2024)
This chapter focuses on the background of study which is on determinants of youth’s voting behaviours among students. The scope ofstudy is focusing on students in UiTM Campus Samarahan 2. Section 1.1 discusses on the Chapter Review, Section 1.2 the background of study, Section 1.3 explains the research objectives, Section 1.4 is the research problem and Section 1.5 states the significance of study. Section 1,6additionally is about the scope ofresearch and Section 1.7 explains about the research questions. In addition to that, Section 1.8 is about the definition of terms and concepts and finally Section 1.9 is on chapter summary.